A new species of tube-dwelling anemone (Cnidaria, Anthozoa, Ceriantharia, Ceriantheopsis) from the Warm Temperate South-western Atlantic - Stampar, Sérgio N. [UNESP]; Scarabino, Fabrizio; Pastorino, Guido; Morandini, André C. (Cambridge University Press (CUP), 2016)
A new species of tube-dwelling anemone of the genus Ceriantheopsis (Cnidaria: Ceriantharia), Ceriantheopsis lineata sp. nov., is described and can be found in fine sand or mud in the sublittoral zone (0-200 m) from Argentina to Brazil (Warm Temperate South-western Atlantic). This new species is distinguished from its congeners by a number of features, however some characters (directive tentacles, line on tentacles and length of P2) allow a conclusive identification among the other Ceriantheopsis species.
Keywords: Anthozoa; Atlantic Ocean; taxonomy